2019
DOI: 10.1108/bfj-06-2019-0452
|View full text |Cite
|
Sign up to set email alerts
|

Food label design – exploring the literature

Abstract: PurposeThe purpose of this paper is to identify the main research fields concerning food label designs and build a topic overview. To this end, the literature review method was chosen.Design/methodology/approachA sample of 121 papers was identified and analyzed using bibliometric analysis. Journals, articles, authors of the sample and the term co-occurrence map, which represents the recurring themes and organizes them in clusters, were defined. To recognize the main research fields, starting from analyzing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…A search in the Web of Science Core Collection [14] shows that there are no documents for the topics "food" and "consumer attitude*" and "bibliometric" and only three studies were found on the Scopus database [15] (for a basic search considering article title, abstract and keywords). The documents found in the Scopus address ethical foods [16], food label design [17] and organic food in China [18]. This highlights that there is a huge gap here in literature which should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…A search in the Web of Science Core Collection [14] shows that there are no documents for the topics "food" and "consumer attitude*" and "bibliometric" and only three studies were found on the Scopus database [15] (for a basic search considering article title, abstract and keywords). The documents found in the Scopus address ethical foods [16], food label design [17] and organic food in China [18]. This highlights that there is a huge gap here in literature which should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of business studies leveraged bibliometric analysis to investigate the literature on different topics, including advertising [40], strategic management [41], food labelling [42], and food policy [43]. However, in the nutrition labelling-related fields, bibliometric analysis, especially co-citation analysis, has not been widely used.…”
Section: Bibliometric Analysis and Centrality Measuresmentioning
confidence: 99%
“…Consumer behaviour [ 19 ] towards F&NL has recently gained significant attention. The food industry is constantly evolving, as are consumers' demands and preferences [ 20 ].…”
Section: Introductionmentioning
confidence: 99%